Capacity of a body shape index and body roundness index to identify diabetes mellitus in Han Chinese people in Northeast China: a cross‐sectional study. Issue 11 (20th August 2018) - Zhao, Q.; Zhang, K.; Li, Y.; Zhen, Q.; Shi, J.; Yu, Y.; Tao, Y.; Cheng, Y.; Liu, Y.
Abstract: Aim: To assess the capacity of a body shape index and body roundness index to identify people with diabetes mellitus and those with prediabetes, and to determine whether a body shape index and/or body roundness index is superior to the traditional overall adiposity index, BMI, in Han Chinese people in Northeast China. Methods: A total of 15 078 participants were enrolled from Jilin province in 2012 using a multi‐stage stratified random cluster sampling method. Demographic data were collected, and anthropometric indices and biochemical indices were measured. Receiver‐operating characteristic curves were used to compare the validity of each anthropometric index, and the area under the receiver‐operating characteristic curve was calculated for each anthropometric index. Results: Body roundness index had the highest areas under the receiver‐operating curve for prediabetes, diagnosed diabetes and undiagnosed diabetes in both men and women (all P <0.01). The optimum threshold values for body roundness index for prediabetes, undiagnosed diabetes and diagnosed diabetes, respectively, were 2.8, 3.7 and 3.3 in men, and 3.4, 3.8 and 3.6 in women. The cumulative proportions of prediabetes, undiagnosed diabetes and diagnosed diabetes identified by the optimum threshold values of body roundness index were 79.2%, 67.5% and 77.0% (82.3%, 62.5% and 75.3% in men; 74.6%, 74.9% and 78.3% in women), respectively. Conclusions: BMI, a body shape index and body roundness index may identify the presence of diabetes. Among the three anthropometric indices, BMI had the weakest association with diabetes. Body roundness index is an alternative index for assessing diabetes in Han Chinese people in Northeast China. What's new?: Visceral adipose tissue (VAT) is remarkably different from subcutaneous adipose tissue (SAT) with regard to physiological functions. An increase in VAT amount is particularly linked to metabolic diseases. The amount and distribution of VAT and SAT determine body shape; we found that body roundness index (BRI) was an alternative index for assessing diabetes mellitus in Han Chinese people in Northeast China. The distinguishing capability of BRI can be integrated into routine clinical care as a simple, convenient and cost‐effective way to monitor the transition from prediabetes to diabetes.